Visualization of Krebet Wood Mask in Visual Arts Learning For PGSD Students: A Study of Creativity Habitus - Probosiwi Probosiwi; Fery Setyaningrum; Dyah Lyesmaya; Lilik Binti Mirnawati; Desiana Muryasari; Dian Effendi (Universitas Negeri Malang, 2023)
This article is research results about making Krebet “batik” masks in groups carried out by PGSD students. Research’s aims to describe the application of Pierre Bourdieu's concept of habitus and Wallas' creative process. Research methodology is qualitative and case study approach. Data collection techniques are observation and document review. Data analysis techniques are data collection, data reduction, data presentation, drawing conclusions and verification. The subjects researched were PGSD FKIP UAD students, while the objects were Krebet wooden batik masks. Results show that: (1) students applying habitus concept in the practice of making “batik” wooden masks (knowledge, understanding, perceptions, values, and actions) that are internalized as part of society in Yogyakarta; (2) students were integrated habitus concept in the stages of the creative process: (a) the preparation stage which is carried out by forming groups and discussing the theme of “batik” motifs; (b) incubation stage, search for inspiration forms explored of motifs following “batik” objects; (c) illumination stage on the surface of the mask with